Bagaimana Inspeksi, Kontrol dan Supervisi mempengaruhi Pembinaan dan Pengembangan dari Pengawas Sekolah: Efek pada Kompetensi Kepala Sekolah - Yayah Rahyasih; Johar Permana; Liah Siti Syarifah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
Improving the quality of educational institution requires adequate competence from a school principal to develop of school he leads, to help improve the professionalism of the principal, the government appoints an education supervisor whose job is to carry out managerial supervision. This research aims to reinforce the impact of spectrums of educational supervision in coaching and development for school principals. The present study adopted a quantitative approach through surveys. The population in this study were all school principals in Bandung, whereas the sample was a member of the population taken through a saturation sampling technique of 39 people. Assessed through multiple linear regression analysis, the current research also examined primary sources of data collected through fulfilling the interviews and questionnaires covering three spectrums of surveillance activities (aspects of inspection, control, supervision) as well as coaching and development for school principals. The results of analysis demonstrated that Fcount is 51.7 with a significance level of 0.000 ≤ 0.05. Thus, it can be concluded that the managerial supervision carried out by supervisors with inspection, control and supervision delivers a positive and significant impact in the coaching and development activities of school principals. This report presented the findings of research that supervisory must be proportionate, planned, directed and sustainable.